2018
DOI: 10.1093/aob/mcy037
|View full text |Cite
|
Sign up to set email alerts
|

Variation in functional responses to water stress and differentiation between natural allopolyploid populations in the Brachypodium distachyon species complex

Abstract: After polyploid formation and/or colonization, B. hybridum populations have adaptively diverged physiologically and genetically in response to variations in aridity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 53 publications
(97 reference statements)
4
20
0
Order By: Relevance
“…S8). Recent analysis of dehydrin gene expression in B. distachyon and its close B. stacei and B. hybridum species have shown that Bdhn3 was strongly up-regulated by drought (>400-fold higher expression in dry-plants compared to control-plants), although the level of induction depended on genotype (Martínez et al, 2018). Our data support these results and additionally demonstrate that drought induction also upregulates the expressions of the Bdhn1a, Bdhn2…”
Section: Dehydrin Expression Induction In Brachypodium Distachyonsupporting
confidence: 89%
See 1 more Smart Citation
“…S8). Recent analysis of dehydrin gene expression in B. distachyon and its close B. stacei and B. hybridum species have shown that Bdhn3 was strongly up-regulated by drought (>400-fold higher expression in dry-plants compared to control-plants), although the level of induction depended on genotype (Martínez et al, 2018). Our data support these results and additionally demonstrate that drought induction also upregulates the expressions of the Bdhn1a, Bdhn2…”
Section: Dehydrin Expression Induction In Brachypodium Distachyonsupporting
confidence: 89%
“…These shared functional responses to drought by orthologous dehydrin genes' induction in both species reinforce the potential of B. distachyon as a model system for cereals, like bread wheat. Our results also highlight the importance of these four dehydrins in the protection of B. distachyon plants to water stress conditions in mature individuals, the developmental stage when they face the most severe drought conditions of their life cycle (Martínez et al, 2018) The drought-induced upregulation of Bdhn genes was significantly different among the studied B. distachyon ecotypes for all four Bdhn genes (Table 4; Fig. 5; Supplementary Fig.…”
Section: Dehydrin Expression Induction In Brachypodium Distachyonmentioning
confidence: 51%
“…Cs can maintain high water content in leaf, and a largely normal rate of photosynthesis and stomatal conductance in dry soil (with 2% water content) (Yan et al ., 2019b). It can survive and recover from prolonged periods of drought (Zhang et al ., 2011), whilst nine weeks of B. distachyon seedlings showed above‐ground plant water content less than 35% after drought stress treatment with 25% soil water content (Martínez et al ., 2018). At the molecular level, complex transcriptional regulatory networks have been revealed, with lncRNAs, miRNAs and conserved DEGs (including TFs) all involved.…”
Section: Discussionmentioning
confidence: 99%
“…These improvements imply a greater resistance to environmental change (Schoenfelder and Fox, 2015). Several studies reported a better adaptivity of polyploid plants to abiotic stress conditions, such as salt (Chao et al, 2013), drought (del Pozo and Ramirez-Parra, 2014;Martínez et al, 2018), drought and heat stress (Godfree et al, 2017), cold (Klatt et al, 2018), and light (Coate et al, 2013). The better stress response and adaptation of polyploids to abiotic conditions are probably under epigenetic control (del Pozo and Ramirez-Parra, 2014).…”
Section: Introductionmentioning
confidence: 99%